2020
DOI: 10.1186/s13561-020-00288-7
|View full text |Cite
|
Sign up to set email alerts
|

Considering the societal perspective in economic evaluations: a systematic review in the case of depression

Abstract: Background Depressive disorders are associated with a high burden of disease. However, due to the burden posed by the disease on not only the sufferers, but also on their relatives, there is an ongoing debate about which costs to include and, hence, which perspective should be applied. Therefore, the aim of this paper was to examine whether the change between healthcare payer and societal perspective leads to different conclusions of cost-utility analyses in the case of depression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 93 publications
0
17
0
Order By: Relevance
“…However, a lack of systematically produced non-health estimates hampers the synthesis of evidence from a valuation and price-setting perspective. Variation in the methods employed to incorporate these non-healthcare perspectives can also be a challenge [44], with results that lead to different conclusions. As better data become available, estimation of non-health effects will improve.…”
Section: Incorporation Of Additional Perspectivesmentioning
confidence: 99%
“…However, a lack of systematically produced non-health estimates hampers the synthesis of evidence from a valuation and price-setting perspective. Variation in the methods employed to incorporate these non-healthcare perspectives can also be a challenge [44], with results that lead to different conclusions. As better data become available, estimation of non-health effects will improve.…”
Section: Incorporation Of Additional Perspectivesmentioning
confidence: 99%
“…Moreover, our findings regarding the inclusion of social costs in all those articles that described an economic evaluation differed from those in similar work carried out on other diseases 84 such as Alzheimer´s disease, 21 where the proportion of social costs in economic evaluations reached more than two-thirds, and depression, where the figure was 42%. 23 By contrast, for DM the percentage of economic evaluation studies which included social costs was close to that in the case of rare diseases, where it was only 11%. 24…”
Section: Discussionmentioning
confidence: 86%
“…By contrast, EEs that include a narrow range of sequelae may underestimate the burden of IMD and its health and economic impact, and thus fail to grasp the cost-effectiveness of IMD interventions, as demonstrated in Beck et al (2021) [ 15 ]. A recent systematic review of economic evaluations in depression has shown that changing from a narrow payer perspective to a broader societal perspective (e.g., considering the burden on caregivers as well as patients) can change the outcome of the analysis and thus affect policy decisions [ 34 ]. Systematic reviews are better suited to capture the burden of disease and thus to be used in EEs, yet they rely on the quality of included studies.…”
Section: Discussionmentioning
confidence: 99%